2008
DOI: 10.1530/rep-07-0548
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of fucosyltransferase 4 in human endometrium

Abstract: It has been suggested that selectin ligands expressed by the endometrial epithelium are essential for the initial adhesion of the blastocyst to the luminal epithelium of human endometrium. One of the enzymes responsible for the production of selectin ligands is fucosyltransferase 4 (FUT4), a member of a1,3 fucosyltransferases. The aims of the present study were to characterize FUT4 mRNA and protein in human endometrium during the menstrual cycle and to investigate the hormonal regulation of FUT4 whose mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Fut4 mRNA expression has been reported to decline over Days 1-5 of pregnancy in mice [45], and blastocysts express the LewisX ligand L-selectin [46]. We have also found that Fut4 mRNA expression is higher in the peri-implantation uterus than at estrus in mice (data not shown), and in human endometrium, Fut4 mRNA and protein expression peak in the early to midand midsecretory phase of the cycle [47,48]. The redundancy in this enzyme family may contribute to the complexity of the molecular regulation of implantation.…”
Section: Discussionsupporting
confidence: 49%
“…Fut4 mRNA expression has been reported to decline over Days 1-5 of pregnancy in mice [45], and blastocysts express the LewisX ligand L-selectin [46]. We have also found that Fut4 mRNA expression is higher in the peri-implantation uterus than at estrus in mice (data not shown), and in human endometrium, Fut4 mRNA and protein expression peak in the early to midand midsecretory phase of the cycle [47,48]. The redundancy in this enzyme family may contribute to the complexity of the molecular regulation of implantation.…”
Section: Discussionsupporting
confidence: 49%
“…Alteration in the fucosylation of integrin avb3 in the uterine epithelial cells may affect its receptive ability to the adhesion of an embryo. The expression of FUT4 mRNA and protein is increased in endometrium tissues during the early and midsecretory stages (23,24). Given that knocking down FUT4 expression by RNAi technology reduces the synthesis of LeY (39), we have transiently transfected FUT4 siRNA into RL95-2 cells and confirmed that suppression of FUT4 expression inhibits the synthesis of LeY and concurrently reduces the adhesion of JAR cells to the RL95-2 cells.…”
Section: Figurementioning
confidence: 73%
“…The glycosylation status of integrin avb3 during implantation is largely unknown. Given that both LeY oligosaccharide and integrin avb3 are significantly increased from early to midsecretory phases of the menstrual cycle in humans (24,27), we hypothesize that integrin avb3 expressed in human endometrial cells may carry oligosaccharide LeY. Using an in vitro implantation model, we demonstrate that both the secretory-stage human endometrial tissue and RL95-2 cells express integrin avb3 which contains LeY.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Based on Lectin analysis, glycobiology of implantation studies have demonstrated that characteristic fucosylated oligosaccharide structures are found at the maternal-fetal interface, indicating that fucosylation promotes the mutual recognition and adhesion of the embryo-endometrium 25 . Both the embryo and endometrium stage-specifically express FUTs, and the specific fucosylated oligosaccharide chains control the implantation functions 26, 27 . In this study, we mainly focused on FUT1, FUT4 and FUT8 which are responsible for catalyzing α1,2-, α1,3- and α1,6-fucosylation, respectively.…”
Section: Introductionmentioning
confidence: 99%